2nd Coatings and Interfaces Web Conference (CIWC-2 2020) 2020
DOI: 10.3390/ciwc2020-06837
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of CrAlN Coating Chemical Composition on Soldering Resistance in Contact with Al-Si-Cu Alloy

Abstract: During the high pressure die casting (HPDC) process the die material is exposed to thermal fatigue, erosion, and corrosion. Corrosion leads to the soldering of cast alloy to tool surfaces which consequently bonds the casting with die material. Besides wear, such a process reduces the casting quality and production efficiency and endangers the tool integrity. Application of thin ceramic coatings on die surfaces reduces the soldering effects and improves the die performance. However, the development of ceramic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Dlatego zalecane jest stopniowe oraz bardzo powolne nagrzewanie płyty. Podczas dobierania profilu lutowniczego należy uwzględnić takie czynniki jak: wytrzymałość temperaturowa układu w obudowie BGA, temperaturę otoczenia, wielkość i grubość płyty PCB, na której znajduje się układ (odprowadzanie ciepła przez jej powierzchnię), stop spoiwa lutowniczego [11][12][13][14].…”
Section: Profil Lutowniczy (Soldering Profile)unclassified
“…Dlatego zalecane jest stopniowe oraz bardzo powolne nagrzewanie płyty. Podczas dobierania profilu lutowniczego należy uwzględnić takie czynniki jak: wytrzymałość temperaturowa układu w obudowie BGA, temperaturę otoczenia, wielkość i grubość płyty PCB, na której znajduje się układ (odprowadzanie ciepła przez jej powierzchnię), stop spoiwa lutowniczego [11][12][13][14].…”
Section: Profil Lutowniczy (Soldering Profile)unclassified
“…Investigations regarding metallic/ceramic multilayer coatings deposited from sectioned targets showed the possibility of obtaining a multilayer CrAl/CrAlN deposited from a Cr: 0.25 and Al: 0.75 area ratio by the magnetron co-sputtering pulsed dc method, as well as its characterization by XRD, XPS, and Raman spectroscopy [9]. Other studies of CrAlN coatings deposited by unbalanced magnetron sputtering and different Cr and Al concentrations from sectioned targets demonstrated a good corrosion resistance and adhesion to substrate when Cr and Al content was increased [20]. However, to our knowledge, there are no published studies of CrAl/CrAlN coatings deposited by HIPIMS on AISI-A11 tool steel of sectioned targets and their mechanical and tribological properties.…”
Section: Introductionmentioning
confidence: 96%
“…In this study, we consider the influence of the defects on the oxidation resistance of the nanolayer (Cr,Al)N coating composed of CrAlN/CrN/CrAlN/AlN nanolayers. This coating was used in our previously published study [31], where we investigated the soldering resistance of such nanolayer hard coatings in contact with molten Al-Si-Cu cast alloy at a temperature of 750 • C. We found that this particular coating reduced the soldering of cast alloy to a steel die applied for high-pressure die casting.…”
Section: Introductionmentioning
confidence: 99%